Performance Comparison of Three Modified Howland Current Source Circuits in Low-Cost Bioimpedance Analyzer for Bio-Phantom Signal Acquisition - Eka Firmansyah; Ridwan Wicaksono (JURNAL INFOTEL, 2025)
Electrical impedance tomography (EIT) supports recent advancements in gastric monitoring for telehealth applications. The challenge in providing low-cost EIT is ensuring a stable current injection over diverse tissue conductivities within the abdominal cavity. Three current source circuits based on Howland's current source are investigated to be applied in a low-cost portable bioimpedance analyzer (p-BIA). Those are: a) triple amplifier Howland current source (TAHCS), b) mirrored Howland current source (MHCS), and c) composite mirrored Howland current source (CMHCS). Evaluation has been conducted based on signal-to-noise ratio (SNR), broadness of the frequency range, and output impedance over frequency value and stability. Due to its high SNR value (82.56 to 102.1 dB), broad (500 Hz to 500 kHz) operating frequency, and consistent output impedance over operating frequency (10 to 25 kÎ©), CMHCS is a good option in realizing p-BIA in gastric monitoring based EIT.